Mental Toughness of Athletes Toward the News Media - Setyawati, Heny; Rahayu, Tandyo; Sugiharto, DYP.; Raharjo, Turnomo (Universitas Negeri Semarang, 2016)
Sports news with its variety is viewed as if â€œa piece of a coinâ€ by the sports coaches and athlete. Therefore, the development and the performance of athletes need to be disclosed to the society in general, through mass media though sometimes uncontrolled news may give negative side effect which is contra productive for the sports coaching, including mental defectiveness of an athlete. This study is to examine mental toughness of athletes toward the news media. The participants were athletes who are from Central java, who are informed in mass media. They are in potential ages with national level achievement. They are experienced in their own expertise of sport within more of 7 years. They are in progress doing training in the training center basecamp and live in dormitory.Â The data were collected from interview. The analysis of data a descriptive qualitative.Â Mass media has an important role for an athlete as a constructive criticism shall be accepted as reality. In fact the critics on the media are helpful in improving her weakness.Athletes actually feel delighted when media covers them. The news in media can boost athletes Â motivation and popularity. Positive news covered in mass media makes them feel proud. News covering the weaknesses of athletes can bring about self-reflection and self-improvement.